A New Dual-Promoter System for Cardiomyocyte-Specific Conditional Induction of Apoptosis. (17th January 2013) - Agostini, Silvia; Lionetti, Vincenzo; Matteucci, Marco; Chiuppesi, Flavia; Giacca, Mauro; Pistello, Mauro; Recchia, Fabio A.
Abstract : Apoptosis is a key determinant of major pathological processes, including chronic cardiac failure. We developed and tested in vitro a novel system to induce cardiomyocyte-specific apoptosis by virus-mediated delivery of a conditional transgene. The entire system was packaged in a lentiviral vector. We used the cardiomyocyte-specific Na + -Ca 2+ exchange promoter to control the transcription of the reverse tetracycline transactivator, while the transgene expression was driven by the tetracycline-responsive element. The proapoptotic transgene of choice was the short isoform of the apoptosis-inducing factor, known to quickly induce the caspase-independent apoptosis when overexpressed in cells. Transduction of cardiomyocyte cells with this vector caused a tetracycline-regulated induction of apoptosis, which was not observed in noncardiac cells. Therefore, our system proved a valuable molecular tool for inducing controlled apoptosis in selected cells. Furthermore, the vector we developed is suitable for "lentivirus transgenesis, " an interesting strategy recently proposed for the genetic manipulation of animals other than mice, including large mammals.